2005
DOI: 10.1086/431601
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Protease and Reverse‐Transcriptase Mutations: Correlations with Antiretroviral Therapy in Subtype B Isolates and Implications for Drug‐Resistance Surveillance

Abstract: Background. It is important, for drug-resistance surveillance, to identify human immunodeficiency virus type 1 (HIV-1) strains that have undergone antiretroviral drug selection.Methods. We compared the prevalence of protease and reverse-transcriptase (RT) mutations in HIV-1 sequences from persons with and without previous treatment with protease inhibitors (PIs), nucleoside RT inhibitors (NRTIs), and nonnucleoside RT inhibitors (NNRTIs). Treatment-associated mutations in protease isolates from 5867 persons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 25 publications
10
99
1
3
Order By: Relevance
“…Table 4, which is published as supporting information on the PNAS web site, shows the number of highly discordant results according to the mutation data set and learning method. For 10,624 predictions obtained by applying LARS to the nonpolymorphic TSM data set, only 33 (0.31%) were highly discordant with the measured phenotype ( Table 5, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4, which is published as supporting information on the PNAS web site, shows the number of highly discordant results according to the mutation data set and learning method. For 10,624 predictions obtained by applying LARS to the nonpolymorphic TSM data set, only 33 (0.31%) were highly discordant with the measured phenotype ( Table 5, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…The most successful approach to external feature selection was to use a set of mutations previously identified as absent in viruses from treatment-naïve individuals and occurring at significantly increased frequencies in viruses from treated individuals (10). This set of nonpolymorphic TSMs had the highest accuracy (80.1%) averaged over the five learning methods when classifying isolates as susceptible, low͞intermediate, and high-level resistant, and had the lowest MSEs compared with the other mutation data sets when used for regression.…”
Section: Discussionmentioning
confidence: 99%
“…This strain was predicted as susceptible to RT inhibitors. Four strains (05BRSAP26, 05BRSAP28, 06BRSAP31, and 06BRSAP33) harbored the polymorphism V179D, which occurs in 3.1% of subtype B-infected drug-naïve subjects and causes potential low-level resistance to each available NNRTI (Rhee et al 2005). Phylogenetic analyses (data not shown) demonstrated that these four strains form a strong monophylectic cluster and were recovered from patients who probably took part in the same chain of viral spread.…”
Section: Discussionmentioning
confidence: 99%
“…TAMs are common in low income countries in which the fixed-dose combinations containing thymidine analogues are the mainstay of therapy (Ross et al, 2001). TAMs are also common in HIV-1 isolates from patients who began therapy in the pre-highly active antiretroviral therapy (HAART) era (De Luca et al, 2006;Rhee et al, 2005). The mutations accumulate in two distinct but overlapping patterns (De Luca et al, 2006;Gonzales et al, 2003;Marcelin et al, 2004b;Yahi et al, 1999).…”
Section: Nrti Tams (Excision)mentioning
confidence: 99%
“…In comparison, L10F/R and A711/L minor mutations do not occur in the absence of PI therapy (Rhee et al, 2003). Additional PI-selected mutations include the highly polymorphic mutations I13V, D60E, I62V, V77I and I93L as well as several uncommon mutations including V11I, E34Q, E35G, K43T, K45I, K55R, Q58E, T74P/A/S, V75I, N83D, P79A/S, I85V, L89V, T91S, Q92K and C95F (Ceccherini-Silberstein et al, 2004;Parkin et al, 2003;Rhee et al, 2005;Svicher et al, 2005;Vermeiren et al, 2007;.…”
Section: Point Mutations Associated With Resistance To Protease Inhibmentioning
confidence: 99%